1989
DOI: 10.1002/j.1939-4640.1989.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship Between Defective Sperm Function and the Generation of Reactive Oxygen Species in Cases of Oligozoospermia

Abstract: The ability of human spermatozoa to exhibit sperm-oocyte fusion in response to the ionophore, A23187, was examined in relation to the capacity of these cells to generate reactive oxygen species. In 70 fertile control donors, there was an overwhelming pattern of high levels of sperm-oocyte fusion associated with low levels of reactive oxygen species production. By contrast, 88% of the 74 oligozoospermic patients exhibited less than 25% oocyte penetration in response to A23187 and 58% exhibited no penetration wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
123
0
4

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(130 citation statements)
references
References 13 publications
3
123
0
4
Order By: Relevance
“…Motility is indispensable for the spermatozoa, as it has to travel the female reproductive tract to reach the site of fertilization. Studies have found that the levels of ROS correlate with the motility of spermatozoa (Aitken et al, 1989a;Iwasaki and Gagnon, 1992;Agarwal et al, 1994;Armstrong et al, 1999). Peroxidative damage to the sperm membrane and axonemal proteins appears to be the cause of permanent impairment in sperm motility .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motility is indispensable for the spermatozoa, as it has to travel the female reproductive tract to reach the site of fertilization. Studies have found that the levels of ROS correlate with the motility of spermatozoa (Aitken et al, 1989a;Iwasaki and Gagnon, 1992;Agarwal et al, 1994;Armstrong et al, 1999). Peroxidative damage to the sperm membrane and axonemal proteins appears to be the cause of permanent impairment in sperm motility .…”
Section: Discussionmentioning
confidence: 99%
“…It attacks the fluidity of sperm plasma membrane, with subsequent loss of the ability for oocyte fusion and fertilization (Mammoto et al, 1996). Human sperm cells in contrast with other cells are particularly susceptible to oxidation of their plasma membranes due to the existence of a high concentration of polyunsaturated fatty acids in the membrane (Aitken et al, 1989a;Jones et al, 1979). PUFA play an important role in ion transport and sperm membrane fluidity, therefore oxidation of sperm membrane PUFA by oxidants (ROS) cause to deficiency in membrane function and sperm death.…”
Section: Introductionmentioning
confidence: 99%
“…For example, low quality cat embryos reduce the developmental potential of co-cultured conspecifics [55]. Thus, it is possible that sub-par embryos secrete development-inhibiting factors, such as radical oxygen species [68,69] known to be detrimental to gamete [70] and embryo [71,72] survival. An important component of oocyte cytoplasmic maturation appears to be certain enzyme transcripts that may protect against reactive oxygen [73].…”
Section: Discussionmentioning
confidence: 99%
“…These cells are particularly susceptible to such stress in view of their high content of unsaturated fatty acids (Jones et al, 1979) and highly specialized capacity for generating reactive oxygen species (ROS), including Superoxide anión and hydrogen peroxide (Aitken & Clarkson, 1987a, b;Alvarez et al, 1987;Aitken et al, 1989). Moreover, a number of retrospective analyses have indicated that the excessive generation of ROS is associated with defective sperm function, particularly oligozoo¬ spermia (Aitken & Clarkson, 1987;Aitken et al, 1989). Furthermore, in a recent prospective study (Aitken et al, 1991), the incidence of spontaneous pregnancy was shown to be negatively correlated with generation of ROS with approximately half of the oligozoospermic patients in the study population (8 of 17) exhibiting increased activity.…”
Section: Introductionmentioning
confidence: 99%